The Rights of Indigenous Peoples in the Development of Tourism Destinations: A Human Rights Perspective (Contrarius Series: Law & Social Justice, 2026)
Indigenous peoples are the ones most capable of determining whether a culture changes. Whether these communities can maintain their customs and traditions in an increasingly modern era will determine if that culture continues to survive. Despite this, in practice, Indigenous peoples are often treated as objects of tourism rather than as subjects or main actors. To address this challenge, an approach that respects participation and collective rights is needed to help Indigenous communities become successful participants in tourism. This research uses a normative legal method to explore possible solutions. Furthermore, tourism development must be grounded in a strong legal foundation, such as Law No. 39 of 1999 on Human Rights, Article 18B, paragraph (2), of the 1945 Constitution, and international principles such as UNDRIP, to protect the rights of Indigenous peoples. With these legal protections and if implemented properly, tourism can serve as a tool for empowerment and cultural preservation through harmonized regulations, meaningful participation, and the active role of Indigenous communities.